2005
DOI: 10.1603/0022-0493-98.3.988
|View full text |Cite
|
Sign up to set email alerts
|

Variation for Resistance to Aphids (Homoptera: Aphididae) Among Tomato Inbred Backcross Lines Derived from Wild <I>Lycopersicon</I> Species

Abstract: Two tomato inbred backcross line (IBL) populations, derived from crosses between aphid-susceptible Lycopersicon esculentum Mill. 'Peto 95-43' X resistant wild L. pennellii Corr (D'arcy) accession LA716, and Peto 95-43 X resistant wild L. hirsutum f. glabratum Mull accession LA407, were evaluated in replicated field experiments for resistance to potato aphid, Macrosiphum euphorbiae (Thomas), and green peach aphid, Myzus persicae (Sulzer). Aphid infestation scores for each IBL and control (LA716, LA407, Peto 95-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…A later study revealed that several isolates of potato aphid and green peach aphid ( Myzus persicae ) can overcome the resistance mediated by Mi ( Meu1 ), limiting the use of this gene for aphid control in tomato [391]. In a more recent study, two tomato BI populations, derived from crosses between two different aphid susceptible L. esculentum lines and two aphid resistant accessions of L. pennellii and L. hirsutum , were evaluated for resistance to both potato aphid and green peach aphid [80]. Field screening over two years resulted in the identification of seven BILs (BC 2 S 3 to BC 2 S 6 ) with resistance to both types of aphid.…”
Section: Mapping Genes and Qtlsmentioning
confidence: 99%
See 1 more Smart Citation
“…A later study revealed that several isolates of potato aphid and green peach aphid ( Myzus persicae ) can overcome the resistance mediated by Mi ( Meu1 ), limiting the use of this gene for aphid control in tomato [391]. In a more recent study, two tomato BI populations, derived from crosses between two different aphid susceptible L. esculentum lines and two aphid resistant accessions of L. pennellii and L. hirsutum , were evaluated for resistance to both potato aphid and green peach aphid [80]. Field screening over two years resulted in the identification of seven BILs (BC 2 S 3 to BC 2 S 6 ) with resistance to both types of aphid.…”
Section: Mapping Genes and Qtlsmentioning
confidence: 99%
“…Unfortunatley, most of these resources have not been characterized or utilized for insect resistance breeding, though a few inheritance studies have been undertaken [70, 77, 78]. Breeding for insect resistance in tomato has generally encountered more difficulties than breeding for disease resistance, linkage drag being a major impediment [34, 72, 79, 80]. It is expected that identification of markers associated with insect resistance and use of MAS will help alleviate some of the difficulties in developing insect resitant cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Average M. persicae population on three leaves from the upper, middle and lower parts of 10 plants per genotype was calculated (Akhtar et al 2010). Genotypes were ranked as highly resistant, resistant and susceptible on the basis of aphid infestation scores following the trinomial sampling scale: 0 ¼ no aphids; 1 ¼ 1-10 aphids and 2 ¼ 11 or more aphids (Kohler and Clair 2005;Akhtar et al 2010). …”
Section: Resistance To Aphid M Persicaementioning
confidence: 99%
“…The populations of M. persicae on three leaves, upper, middle and lower parts of 10 plants per genotypes, were recorded. Genotypes were ranked as highly resistant, resistant and susceptible on the basis of aphid infestation scores following the trinomial sampling scale; 0 = no aphids (highly resistant); 1 = 1-10 aphids per leaf (resistant) and 2 = 11 or more aphids per leaf (susceptible) (Kohler and St. Clair 2005).…”
Section: Mechanical Inoculationmentioning
confidence: 99%